The Future of Ocean Governance and Capacity Development Essays in Honor of Elisabeth Mann Borgese (1918-2002) (Brill, 2018)
The International Ocean Institute - Canada has compiled more than 80 insightful essays on the future of ocean governance and capacity development, based largely on themes of its Training Program at Dalhousie University in Canada, to honor the work of Elisabeth Mann Borgese (1918-2002). Readership: The essays cover a broad range of ocean governance and capacity development issues and explore future benefits and challenges. This essential collection is aimed at professionals, students and citizens alike.